Universalism, Pluralism, and the Good: Nussbaum’s Capabilities and Finnis’s Basic Goods - Sławiński, Maciej (Hybris, 2018)
Is it possible that Nussbaum’s capability approach and Finnis’s natural law theory have anything in common? We usually do not think ethical pluralism and an account of objective good to be members of one family of theories. Nevertheless there is a set of ideas that Nussbaum and Finnis apparently, and surprisingly, share. Both authors elaborate a list of values which plays a central role in their theory. Careful examination of these lists provides us with many similarities in terms of concepts, terminology and interpretation. Finnis and Nussbaum both employ the ideas of practical reason and intuition, or self-evidence, to reject the academic requirement for theoretical proof of normative approach in morality, philosophy of law and political theory. In this way, they both seek to secure their claims to universality.